Efficient T-EMS Based Decoding Algorithms for High-Order LDPC Codes - Tian, Jing; Song, Suwen; Lin, Jun; Wang, Zhongfeng (IEEE access, 2019)
Non-binary low-density parity-check (NB-LDPC) codes show larger coding gain and lower error floor than their binary counterparts in many cases. However, the existing soft decoding algorithms of NB-LDPC codes generally suffer from high computational complexity. Recently, the trellis-based extended min-sum (T-EMS) decoding algorithm has attracted much attention since it can achieve good decoding performance with high parallelism and low computational complexity. In this paper, we propose two new methods to further reduce the computational complexity and enhance the decoding performance. Firstly, we introduce, with theoretical justification, a universal scheme called threshold-based shrinking (TS) scheme, which facilitates significant reduction of computational complexity for decoding of NB-LDPC codes. Secondly, we present a modified two-extra-column (TEC) scheme and apply it to the T-EMS. Furthermore, a high-performance low-complexity decoding algorithm, named TEC-TEMS algorithm, is obtained. Combining the TS scheme with the TEC-TEMS, the new algorithm, named TS-TEC-TEMS algorithm, achieves much lower computational complexity and has negligible performance loss compared to the TEC-TEMS. For a 256-ary (256, 203) example code, compared to the T-EMS, the computational complexities of the TEC-TEMS and TS-TEC-TEMS algorithms are reduced by more than 50% and nearly 90%, respectively. Moreover, the TEC-TEMS and TS-TEC-TEMS both outperform the T-EMS by about 0.3dB when the frame error rate (FER) is around 10 −5 .